Análisis crítico de la política criminal y del tipo de injusto del delito fiscal en el perú - Yon Ruesta, Roger (2013)
In Peru, successive governments have designed their tax collection policy on the basis of the formal sector without addressing the issue of the informal sector, because of the lack of a plan on criminal tax policy. However, this creates a problem of regularization of tax and criminal policy and a space for the commission of tax offenses. In the present article, the authors do research about the subject, noting that when legislators create incentives for the management of economic strategies, it produces an undesirable effect: it creates room for unfair tax crime. Therefore, we should seek to analyze the political-criminal aspects of the offenses listed above, based on a study of the work of the criminal law on taxation.